2021
DOI: 10.1245/s10434-021-10187-8
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Phase I/II, Open-Label Pilot Trial to Assess the Safety of Hyperthermic Intraperitoneal Chemotherapy After Oncological Resection of Pancreatic Adenocarcinoma

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is a common fatal disease with unfavorable prognosis, even after oncological resection. To improve survival, adding hyperthermic intraperitoneal chemotherapy (HIPEC) has been suggested. Whether HIPEC entails disproportional short-term mortality is unknown and a prospectively determined adverse events profile is lacking. Since both pancreatic resection and HIPEC may relevantly influence morbidity and mortality, this uncontrolled single-arm, open-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…At present, the safety and efficacy of intraperitoneal chemotherapy with gemcitabine in resected PDA patients is under investigation. 91 Moreover, the pharmacokinetics of preoperatively administered intraperitoneal 5-FU in patients with resectable PDA was further studied. 92 With the development of innovative technology, 64 Cu-intraperitoneal radioimmunotherapy (ipRIT) with 64 Cu-labeled antiepidermal growth factor receptor antibody cetuximab as an adjuvant treatment after PDA surgery was investigated in a preclinical mouse model and showed effective results.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the safety and efficacy of intraperitoneal chemotherapy with gemcitabine in resected PDA patients is under investigation. 91 Moreover, the pharmacokinetics of preoperatively administered intraperitoneal 5-FU in patients with resectable PDA was further studied. 92 With the development of innovative technology, 64 Cu-intraperitoneal radioimmunotherapy (ipRIT) with 64 Cu-labeled antiepidermal growth factor receptor antibody cetuximab as an adjuvant treatment after PDA surgery was investigated in a preclinical mouse model and showed effective results.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Meanwhile, Yamada et al 90 launched another phase I/II study and further confirmed the efficacy of intraperitoneal paclitaxel treatment. At present, the safety and efficacy of intraperitoneal chemotherapy with gemcitabine in resected PDA patients is under investigation 91 . Moreover, the pharmacokinetics of preoperatively administered intraperitoneal 5‐FU in patients with resectable PDA was further studied 92 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In this regard, this present trial might even be regarded as an example for future treatment attempts. 6 FUNDING Open Access funding enabled and organized by Projekt DEAL. DISCLOSURE M.W.L.…”
Section: Futurementioning
confidence: 99%
“…Accordingly, this trial attests to the safety of HIPEC application after PDAC resection, which is reassuring. 6 …”
Section: Presentmentioning
confidence: 99%
See 1 more Smart Citation